Rethinking the War against Iraq - McCutcheon, Richard (Anthropologica, 2022)
A conventional view of contemporary Iraq suggests that there were two short wars in 1991 and 2003 between Iraq and a US led cohort of countries separated by an interval of relative peace. This article proposes an alternate view, arguing that the war against Iraq was one continuous war that began in 1991 and ended in 2003. An expanded concept of violence bridging two divergent literatures—the anthropology of war and the ethnography of violence—is used as a lens to see the war with greater definition. The concept of violence put forward identifies the substance of war and is comprised of three conceptual constellations: direct/physical violence, structural/economic violence and cultural/symbolic violence. Each conceptual constellation is illustrated with examples from the war against Iraq drawn from my experience of living in the country and extensive historical research.